Local Ablative Treatment Improves Survival in ESCC Patients With Specific Metastases, 2010–2016: A Population-Based SEER Analysis - Yang, Hui; Wang, Kunlun; Li, Yan; Li, Shenglei; Yuan, Ling; Ge, Hong (Frontiers in Oncology, 2022)
Background We aimed to explore the role of local ablative treatment (LAT) in metastatic esophageal squamous cell cancer (ESCC) patients who received chemotherapy and identify patients who will most likely benefit. Methods We analyzed data of metastatic ESCC patients from the Surveillance, Epidemiology, and End Results (SEER) database between 2010 and 2016. The chi-square test was used to evaluate the unadjusted clinicopathological categorical variables between the two groups. Univariate and multivariate Cox regression analyses were conducted to identify independent prognostic factors of overall survival. Propensity score matching (PSM) was used to adjust the differences between the two groups. Results Overall, 720 metastatic ESCC patients treated with chemotherapy were analyzed in this study; 63.2% of patients (n = 455) received LAT, including radiotherapy (n = 444), primary site surgery (n = 12), or lymph node dissection (n = 27). Gender (HR = 1.220, 95% CI: 1.024–1.453, p = 0.026), bone metastases (HR = 1.559, 95% CI: 1.292–1.882, p < 0.001), and liver metastases (HR = 1.457, 95% CI: 1.237–1.716, p < 0.001) were independent prognostic factors in the entire population. However, LAT was not an independent prognostic factor. Further subgroup analyses showed that LAT improved OS from 8.0 months to 10.0 months in patients with metastases other than bone/liver (HR = 0.759, 95% CI: 0.600–0.961, p = 0.022). LAT was not a prognostic factor in patients with bone/liver metastases (HR = 0.995, 95% CI: 0.799–1.239, p = 0.961). After PSM, the median OS was 8.0 months (95% CI: 7.2–8.8 months) and patients who received LAT had a better OS than patients without LAT (HR = 0.796, 95% CI: 0.653–0.968, p = 0.023). Patients with metastases other than bone/liver could benefit from LAT compared with those with bone/liver metastases. Conclusions Our study indicated that metastatic ESCC patients with metastases other than bone/liver could derive additional benefit from LAT with systemic chemotherapy.